2010
DOI: 10.1002/da.20776
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of posttraumatic stress symptoms in utility workers deployed to the World Trade Center following the attacks of September 11, 2001

Abstract: Nonrescue workers deployed to a disaster site are at risk for PTSD and depression. Extent of exposure affected the most vulnerable workers differently than the least vulnerable ones. These results suggest that the relationship among predictors of PTSD may be different for different vulnerability groups, and underscore the importance of screening, education, and prevention programs for disaster workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 34 publications
2
52
0
3
Order By: Relevance
“…This sample comprises 2,960 WTC disaster recovery utility workers who were assessed at their workplace through the Weill Cornell 9/11 Screening Program (see Cukor et al, 2011;Difede, Roberts, Jayasinghe, & Leck, 2006 for greater detail). During the course of their work assisting in clean-up and utility service restoration, these individuals were exposed to the excavation of human remains and the danger of working within and on top of unstable structures, in an environment at high risk for another attack.…”
Section: E T H O D Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sample comprises 2,960 WTC disaster recovery utility workers who were assessed at their workplace through the Weill Cornell 9/11 Screening Program (see Cukor et al, 2011;Difede, Roberts, Jayasinghe, & Leck, 2006 for greater detail). During the course of their work assisting in clean-up and utility service restoration, these individuals were exposed to the excavation of human remains and the danger of working within and on top of unstable structures, in an environment at high risk for another attack.…”
Section: E T H O D Subjectsmentioning
confidence: 99%
“…Perceptions of safety may also play a role, since those 9/11 disaster workers who had greater exposure reported lower perceived safety, which was in turn associated with greater intrusion and hyperarousal PTSD symptoms as well as depressive symptoms (Fullerton, Ursano, Reeves, Shigemura, & Grieger, 2006). Additionally, disaster workers who perceived their lives were in danger were more likely to report PTSD symptoms (Cukor et al, 2011).…”
mentioning
confidence: 97%
“…Although several studies have found an association between exposure and post-traumatic symptoms (Hansen et al, 2013; Heir, Blix, & Knatten, 2016), other studies did not find such association (Bleich et al, 2003; Ford et al, 2007). Subjective perception of threat is a good predictor of probable PTSD (Cukor et al, 2011). These findings point towards the importance of the subjective perception of threat by such attacks.…”
Section: Introductionmentioning
confidence: 99%
“…The targets of these attacks were workplaces housing large numbers of employees—the intent of terrorism is to cause widespread fear and distress (Vineburgh, 2004). Epidemiologic research on the mental health effects of the 9/11 terrorist attacks on New York City (Breslau, Bohnert and Koenen, 2010), in contrast to prior disaster mental health research, has largely focused on populations not confined to those directly exposed to immediate danger in the disaster (Schuster et al, 2001; Galea et al, 2002; Schlenger et al, 2002; Silver et al, 2002; DeLisi et al, 2003; Boscarino et al, 2004; Stein et al, 2004; DiGrande et al, 2008); many other studies have examined rescue and recovery workers (Smith et al, 2004; Jayasinghe et al, 2005; Elhai et al, 2006; Evans et al, 2006; Katz et al, 2006; Long, Meyer and Jacobs, 2007; Jayasinghe et al, 2008; Stellman et al, 2008; Evans et al, 2009; Berninger et al, 2010; Chiu et al, 2010; Cukor et al, 2010). This body of work points to substantial widespread distress and psychiatric symptoms in these populations.…”
Section: Introductionmentioning
confidence: 99%